2012
DOI: 10.1121/1.4765083
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for generating peaks and notches of head-related transfer functions in the median plane

Abstract: It has been suggested that the first spectral peak and the first two spectral notches of head-related transfer functions (HRTFs) are cues for sound localization in the median plane. Therefore, to examine the mechanism for generating spectral peaks and notches, HRTFs were calculated from four head shapes using the finite-difference time-domain method. The comparison between HRTFs calculated from the whole head and the pinna-related transfer functions calculated from the segmented pinna indicated that the pinna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…26 Regularization was used to limit filter gains if perceptually required: HpTFs typically show distinct notches at high frequencies which are most likely caused by anti-resonances of the pinna cavities. 33 For an example see Fig. 2 (top) at approximately 10 and 16 kHz.…”
Section: Postprocessingmentioning
confidence: 99%
“…26 Regularization was used to limit filter gains if perceptually required: HpTFs typically show distinct notches at high frequencies which are most likely caused by anti-resonances of the pinna cavities. 33 For an example see Fig. 2 (top) at approximately 10 and 16 kHz.…”
Section: Postprocessingmentioning
confidence: 99%
“…The boundary element method (BEM) has been used to calculate HRTFs in a number of studies (Katz, 2001;Kahana and Nelson, 2006;Kreuzer et al, 2009). The results of numerical calculations by the finite-difference time-domain (FDTD) method, which is much faster than the BEM, revealed that the fundamental spectral feature of the HRTF of an individual listener can be calculated from the baffled pinna (Takemoto et al, 2012). At the present, however, neither the BEM nor the FDTD method is available for ordinary listeners because special equipment, e.g., a functional magnetic resonance imaging system, is required to digitize the complicated shape of the pinnae of an individual listener.…”
Section: Introductionmentioning
confidence: 99%
“…For DX ¼ 2.35 mm, axial and diagonal wave packets with f max ¼ 12.18 kHz will almost be in antiphase (E s g ¼ 48%). While such scenarios are unlikely to substantially affect the not-fully-understood mechanism 17 that generates spectral cues, uncertainty still persists. Therefore, the analyzed bandwidth is considered a parameter in the analysis.…”
Section: A Quantifying Voxelization Influencementioning
confidence: 99%
“…Nonetheless, the reported variance issue is expected to become insignificant as the voxel is greatly reduced in size. It is noted that similar issues may arise when the voxel-based geometry results from an MRI scan; although the geometry-grid misalignment of the geometry is less of an issue due to the reduced grid sizes generally used, 15,17 either scanner parameters or voxel processing algorithms may influence the FDTD-simulated acoustic field significantly.…”
mentioning
confidence: 99%
See 1 more Smart Citation